1983
DOI: 10.2331/suisan.49.1437
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the utilization of full-fat soybean and solvent extracted soybean meal in a complete diet for rainbow trout.

Abstract: An experimental feeding trial was conducted with rainbow trout to compare the nutritive value of five commercially available soybean meals (puffed full-fat soybean, toasted full-fat soybean , hexane extracted soybean, extruded hexane extracted soybean and alcohol extracted soybean) as a partial replacement for Peruvian fish meal in a practical ration. The dietary level of Peruvian fish meal was reduced from 35% to 10% and the level of soybean meal increased from 0% to 50% , replacing up to 75% of the Peruvian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 4 publications
1
30
2
Order By: Relevance
“…Dehulled SBM as the sole protein source may lead to growth arrest and increased mortality in rainbow trout, Oncorhynchus mykiss (Dabrowski et al, 1989;. Full-fat SBM, however, appears to support better growth than solvent-extracted SBM in rainbow trout (Smith, 1977;Tacon et al, 1983;Oliva-Teles et al, 1994; and Atlantic salmon, Salmo salar (Olli et al, 1994b). Dehulled, solvent-extracted SBM caused similar negative effects on growth and nutrient digestibility in Atlantic salmon as SBM produced from hulled soybeans (Olli et al, 1994b).…”
Section: Legumesmentioning
confidence: 98%
See 1 more Smart Citation
“…Dehulled SBM as the sole protein source may lead to growth arrest and increased mortality in rainbow trout, Oncorhynchus mykiss (Dabrowski et al, 1989;. Full-fat SBM, however, appears to support better growth than solvent-extracted SBM in rainbow trout (Smith, 1977;Tacon et al, 1983;Oliva-Teles et al, 1994; and Atlantic salmon, Salmo salar (Olli et al, 1994b). Dehulled, solvent-extracted SBM caused similar negative effects on growth and nutrient digestibility in Atlantic salmon as SBM produced from hulled soybeans (Olli et al, 1994b).…”
Section: Legumesmentioning
confidence: 98%
“…Soybeans (Glycine max) Soybean meal (SBM) is one of the most commonly used protein sources in animal feeds due to its high protein content and favourable amino acid profile. However, even when heat-treated, standard (solvent-extracted) and full-fat SBM-containing feeds were supplemented with limiting amino acids, decreased growth in salmonids was observed (Sandholm et al, 1976;Tacon et al, 1983;Davies and Morris, 1997). More specifically, SBM inclusion in the diet causes lower feed intake, weight gain, fecal dry matter, and energy and fat digestibilities in all salmonid species studied (Dabrowski et al, 1989;Olli et al, 1994b;Refstie et al, 1997 andStorebakken et al, 1998;Arndt et al, 1999;Burrells et al, 1999;.…”
Section: Legumesmentioning
confidence: 99%
“…Tacon et al 19) reported that commercial hexane extracted SBM could be used to replace fish meal for up to 50% (26% SBM in the diet) in the diet for rainbow trout, with no adverse effects on growth perform ance or feed utilization efficiency. The same au thors also found that extrusion of that SBM did not improve growth or feed utilization.…”
Section: Growth and Feed Preformancementioning
confidence: 99%
“…In Japan, an alternative protein source for fish meal has been the focus of attention in recent years because of falling catches of sardine which are the main ingredients in the diet, and studies on substitutional protein sources have been started with the yellowtail. 1-7) Many papers have been written on substitutional protein sources with various kinds of fish such as rainbow trout, [8][9][10][11][12] carp, 13-16) tilapia, 17,18) and catfish. 19,20) However, in formation on flatfish is scarce.…”
mentioning
confidence: 99%